A boy with limping pain: a diagnosis not to be missed - Hassan, Radhiana; Jamani, Nurjasmine Aida; Abdul Razak, Ardilla Hanim (Official Journal of Faculty of Medicine, Universiti Teknologi MARA, 2023)
Post traumatic limp in children and adolescent is one of the common reasons seen in primary care. However, making the correct diagnosis is not always easy for primary care physicians. This is because the signs are not specific and the radiological image may appear very subtle to the untrained eyes. Most of the time the causes are not serious and involves soft tissue injury, but at times an important condition could be missed in an inexperienced physician. This paper presents the case of a 16-year-old boy with Slipped Capital Femoral Epiphysis (SCFE) which was overlooked. This case highlights the importance of recognizing the signs of SCFE to allow for early referrals for proper management and prevent its possible complications.